A Delphi consensus statement for the management of post-COVID interstitial lung disease. Issue 9 (2nd September 2022) - Hadda, Vijay; Suri, Tejas M; Iyer, Hariharan; Jain, Avinash; Mittal, Saurabh; Madan, Karan; Mohan, Anant; Seith Bhalla, Ashu; Sindhwani, Girish; Dutt, Naveen; Venkatnarayan, Kavitha; Nath, Alok; et al.
ABSTRACT: Introduction: As millions of people worldwide recover from COVID-19, a substantial proportion continue to have persistent symptoms, pulmonary function abnormalities, and radiological findings suggestive of post-COVID interstitial lung disease (ILD). To date, there is limited scientific evidence on the management of post-COVID ILD, necessitating a consensus-based approach. Areas covered: A panel of experts in pulmonology and thoracic radiology was constituted. Key questions regarding the management of post-COVID ILD were identified. A search was performed on PubMed and EMBASE and updated till 1 March 2022. The relevant literature regarding the epidemiology, pathophysiology, diagnosis and treatment of post-COVID ILD was summarized. Subsequently, suggestions regarding the management of these patients were framed, and a consensus was obtained using the Delphi approach. Those suggestions which were approved by over 80% of the panelists were accepted. The final document was approved by all panel members. Expert opinion: Dedicated facilities should be established for the care of patients with post-COVID ILD. Symptom screening, pulmonary function testing, and thoracic imaging have a role in the diagnosis. The pharmacologic and non-pharmacologic options for the management of post-COVID ILD are discussed. Further research into the pathophysiology and management of post-COVID ILD will improve our understanding of this condition.